Characterizing heterogeneity in the progression of Alzheimer's disease using longitudinal clinical and neuroimaging biomarkers. Issue 1 (10th August 2018) - Goyal, Devendra; Tjandra, Donna; Migrino, Raymond Q.; Giordani, Bruno; Syed, Zeeshan; Wiens, Jenna
Abstract: Introduction: Models characterizing intermediate disease stages of Alzheimer's disease (AD) are needed to inform clinical care and prognosis. Current models, however, use only a small subset of available biomarkers, capturing only coarse changes along the complete spectrum of disease progression. We propose the use of machine learning techniques and clinical, biochemical, and neuroimaging biomarkers to characterize progression to AD. Methods: We used a large multimodal longitudinal data set of biomarkers and demographic and genotype information from 1624 participants from the Alzheimer's Disease Neuroimaging Initiative. Using hidden Markov models, we characterized intermediate disease stages. We validated inferred disease trajectories by comparing time to first clinical AD diagnosis. We trained an L2‐regularized logistic regression model to predict disease trajectory and evaluated its discriminative performance on a test set. Results: We identified 12 distinct disease states. Progression to AD occurred most often through one of two possible paths through these states. Paths differed in terms of rate of disease progression (by 5.44 years on average), amyloid and total‐tau (t‐tau) burden (by 10% and 69%, respectively), and hippocampal neurodegeneration ( P  < .001). On the test set, the predictive model achieved an area under the receiver operating characteristic curve of 0.85. Discussion: Progression to AD, in terms of biomarker trajectories, can be predicted based on participant‐specific factors. Such disease staging tools could help in targeting high‐risk patients for therapeutic intervention trials. As longitudinal data with richer features are collected, such models will help increase our understanding of the factors that drive the different trajectories of AD.